PENGARUH KUALITAS PRODUK, CITRA MEREK, PERSEPSI HARGA DAN DAYA TARIK IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK LIPSTICK WARDAH (STUDI PADA MAHASISWA UNIVERSITAS STIKUBANK SEMARANG) - Nira Widi Pamula, 15.05.51.0090; Maskur, Ali (Students' Journal of Economic and Management, 2019)
The development of business dynamics is increasingly challenging so that business people must be able to make these challenges an opportunity to be able to compete and survive in the future. The purpose of this study was to examine and analyze the effect of product quality, brand image, price perception, and advertisement appeal on purchasing decisions for wardah lipstick products. The population in this study were all students of Stikubank University Semarang who had made the decision to purchase wardah lipstick products. The sample used was 100 respondents, using purposive sampling sampling method. The method of analyzing research data uses multiple linear regression. The results of this study indicate that product quality, brand image, price perception, and ad attractiveness have a positive and significant effect on purchasing decisions for wardah lipstick products.